Hope, Emotional Charges, and Online Action: An Experimental Study of the DREAM Act. (12th January 2021) - Elliott-Negri, Luke; Tu, Siqi; Zheng, Wenjuan; Lennon, Mary Clare
Abstract: This study investigates the causal relationship between an under-studied emotion—hope—and online action. We ask whether some emotions are more effective than others in driving a semi-behavioral outcome—clicking a hyperlink. Using an experimental design, we find that a recorded speech that has been "emotionally charged" with hope increases respondents' willingness to seek information about a contentious social issue, immigrant rights. We argue that the hope charge is uniquely powerful, in part because it energizes both beneficiary constituents (BCs) and conscience constituents (CCs) of social movements, as well as those of broader publics. We suggest that hope is a quintessential bridging charge, linking beneficiary constituents to these other groups. Our study builds on important methodological trends in the developing field of survey experimentation: it uses audio recordings to convey emotional charges and embeds a semi-behavioral measure at the conclusion of an internet-based survey experiment. We argue that hope has been empirically submerged in the discipline, and, when used to charge social movement frames, has under-acknowledged mobilizing power.